The immortal Nicholas - Beck, Glenn (New York : Threshold Editions/Mercury Radio Arts, 2015)
"A thrilling new holiday novel from #1 New York Times bestselling author Glenn Beck"--
"Bestselling author Glenn Beck re-tells the story of Santa Claus, imagining him at the first Christmas and casting him as a guardian for the infant and adult Jesus"--
From the snowy mountains of Western Asia, to the deserts of Egypt, to Yemen's elusive frankincense-bearing boswellia trees, this is an epic tale that gives the legend of Santa a long overdue Christ-centered mission
Keywords: Nicholas, -- Saint, Bishop of Myra -- Fiction; Santa Claus -- Fiction; Christmas stories